Zero-fluoroscopy catheter ablation for arrhythmias in pregnancy: validation of a standardized approach with 5-year follow-up - Sebastian Stec; Marek Bronisz; Joanna Kornaszewska; Katarzyna Styczkiewicz; Marcin Nosal; Alicja Hajduk-Hejnar; Anna Kustroń; Szymon Stec; Agata Bielecka-Dąbrowa; Marta Kornaszewska; Janusz Śledź (Frontiers in Cardiovascular Medicine, 2026)
Background Increasing experience with zero- (ZF) or near-zero fluoroscopy catheter ablation (CA) supports the implementation of an early fluoroless approach for recurrent, symptomatic arrhythmias during pregnancy. Aim This study evaluated the feasibility, efficacy, and safety of CA using a standardized ZF approach during pregnancy. Methods Data were derived from a large, prospective multicenter registry (ELEKTRO-RARE-A-CAREgistry). Between 2012 and 2019, more than 2,655 CA procedures were performed in women using an intention-to-treat ZF approach. The procedures were performed using (1) femoral access, (2) a double-catheter technique without intracardiac echocardiography, (3) an electroanatomic mapping system for mapping and navigation, and (4) conscious light sedation. A shared decision-making approach was applied, including consultation with a pregnancy heart team. Results The study group consisted of 18 consecutive pregnant women without structural heart disease (mean age: 30.6 ± 4.7 years; range: 20–38 years). The mean gestational age at the time of CA was 20.2 ± 9.5 weeks (range: 7–37 weeks), representing <0.01% of all female patients referred for CA. During 18 index procedures, a total of 21 arrhythmogenic substrates were ablated. The major indications for CA during pregnancy were atrioventricular nodal reentrant tachycardia ( n = 10), orthodromic atrioventricular reentrant tachycardia ( n = 2), focal idiopathic ventricular arrhythmia ( n = 5), atrial tachycardia ( n = 2), and atrial fibrillation (AF; n = 1). In the patient with AF, general anesthesia and transesophageal echocardiography were used to guide ZF transseptal puncture and isolation of the right pulmonary veins, where focal AF triggers were identified. All the procedures were successfully completed without fluoroscopy and without serious maternal or fetal complications. The mean procedure and ablation application times were 51.5 ± 6.8 min and 394 ± 338 s, respectively. In one patient, CA of a second premature ventricular contraction focus was postponed until after delivery. After a 5-year follow-up, no adverse effects related to CA performed during pregnancy were observed in the children, and CA was effective in 80% of the women. Conclusions The implementation of a pregnancy heart team and a standardized fluoroless protocol for CA in routine electrophysiological practice enables safe and effective ablation of maternal supraventricular tachycardia and idiopathic ventricular arrhythmias during pregnancy.